2019
DOI: 10.1159/000497253
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Exploratory RCT of Polyethylene Wrap for Heat Loss Prevention in Infants Born at Less than 24 Weeks’ Gestation

Abstract: Background: The treatment effect of occlusive wrap applied immediately after delivery in infants born 24–28 weeks’ gestation has been studied, but the effect is not known in infants born at less than 240/7 weeks’ gestation. Objectives: To determine if the use of occlusive wrap applied immediately after birth in infants born at less than 240/7 weeks’ gestation results in any differences in outcomes when compared to non-wrapped infants. Methods: Parallel exploratory ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 16 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…A total of 6154 titles and abstracts were screened, of which 34 studies that enrolled 3688 neonates were included (eFigure 1 in the Supplement). Among the 34 studies were 4 three-armed RCTs . The mean gestational age of the neonates was 29 weeks, and their mean birth weight was 1200 g (eFigures 2 and 3 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 6154 titles and abstracts were screened, of which 34 studies that enrolled 3688 neonates were included (eFigure 1 in the Supplement). Among the 34 studies were 4 three-armed RCTs . The mean gestational age of the neonates was 29 weeks, and their mean birth weight was 1200 g (eFigures 2 and 3 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-two studies (94%), which involved 3568 neonates, reported the primary outcome of core body (axillary or rectal) temperature at admission or within 2 hours of life . Eight interventions, including routine care, were evaluated in these 32 studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abou et al 52 ".for 22-23 + 6 we do resuscitation in some cases based on an internal pathway and guidelines looking at maternal history and the best interest of that fetus/baby (limits of viability pathway and guidelines); thus we decided to exclude, as not all would receive resuscitation." Reilly et al 228 "Our decision to exclude these infants £23 weeks of gestation. from the main study was because of their much higher mortality rate (mortality was our primary outcome).…”
Section: Discussionmentioning
confidence: 99%